2019
DOI: 10.1590/1807-1929/agriambi.v23n4p291-296
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate and potassium fertilization on agronomic and physico-chemical characteristics and bioactive compounds of eggplant

Abstract: Eggplant is a functional food rich in antioxidants and its consumption brings several benefits to human health. Phenolic compounds and anthocyanins are some of the compounds that interfere in this antioxidant capacity and may be influenced by the mineral nutrition of the plant. The objective was to analyze the effects of potassium and phosphate fertilization on the agronomic and physico-chemical characteristics and bioactive compounds of eggplant fruits. The work was carried out at the Taboquinha Farm, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
1
2
2
Order By: Relevance
“…The most interesting correlations for leaf analysis and antioxidant capacity of cherry fruits was the negative correlation of leaf boron content (L_B) with DPPH, validating the importance of soil boron on the antioxidant capacity of cherry fruits, and the correlation of leaf potassium content (L_K) with the FCR (Table 4). The latter agrees with Oliveira et al [23], who showed that potassium fertilization in greater amounts than optimum for maximum growth and yield, promoted the development of phenolic compounds in plants. Potassium levels were above the optimum for obtaining the maximum yield for almost all cherry trees in the two experimental areas (data not presented here).…”
Section: Discussionsupporting
confidence: 92%
“…The most interesting correlations for leaf analysis and antioxidant capacity of cherry fruits was the negative correlation of leaf boron content (L_B) with DPPH, validating the importance of soil boron on the antioxidant capacity of cherry fruits, and the correlation of leaf potassium content (L_K) with the FCR (Table 4). The latter agrees with Oliveira et al [23], who showed that potassium fertilization in greater amounts than optimum for maximum growth and yield, promoted the development of phenolic compounds in plants. Potassium levels were above the optimum for obtaining the maximum yield for almost all cherry trees in the two experimental areas (data not presented here).…”
Section: Discussionsupporting
confidence: 92%
“…However, the results of the current study surpassed those of other studies on eggplant cultivation (Radicetti et al, 2016;Çolak et al, 2018;Oliveira et al, 2019). Eggplant is one of the vegetables (fruits) with low acidity, with a pH greater than or equal to 4.5 (Oliveira et al, 2019). In the present study, pH values were above 4.9, and SS values ranged from 4.6 to 4.8.…”
Section: Resultscontrasting
confidence: 75%
“…According to Tukey's test, the treatments and irrigation percentages tested did not cause significant variation in the values of the studied variables, especially for pH, SS, TA, SS/ TA and firmness (Table 4). However, the results of the current study surpassed those of other studies on eggplant cultivation (Radicetti et al, 2016;Çolak et al, 2018;Oliveira et al, 2019). Eggplant is one of the vegetables (fruits) with low acidity, with a pH greater than or equal to 4.5 (Oliveira et al, 2019).…”
Section: Resultscontrasting
confidence: 69%
“…A prática da adubação torna-se um fator importante para se obter a qualidade desejada de sementes. A aplicação é positiva e exerce influência sobre processos bioquímicos e fisiológicos das plantas, contribuindo com a produção e qualidade das sementes, promove um melhor desenvolvimento vegetativo das plantas e melhores condições de suprimentos dos frutos e sementes que serão formados (OLIVEIRA et al, 2019).…”
Section: Introductionunclassified